(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
In this article, the terms in the artistic text, agricultural terms, their linguopoetic and linguocultural characteristics, the artistic thinking of the creator, the realization of the linguopoetic goal, therefore, it is appropriate to determine the semantic characteristics of agricultural terms, such as words, in the context of the text. will be discussed separately.